Alignment of business and information strategies and its impact on business performance - Johansson, Björn; Sudzina, František; Pucihar, Andreja (Journal of Business Economics and Management, 2014)
Alignment between business strategy and information strategy has been focused on for several years with research suggesting different explanations to how this alignment influences a firm's performance. This article presents results from an investigation of firms in Slovenia about how business people perceived their business strategy and information strategy to be aligned. Respondents’ statements from the questionnaire survey on their perceived alignment between business strategy and information strategy were checked against the firms’ revenue growth. The analysis of perceived alignment between business strategy, information strategy, and revenue growth shows that there is a significant relationship between alignment and revenue growth in Slovenia, and this link is positive. Managers should aim to align business and information strategies in order to achieve better business performance.